Community-Based Design: The Democratization of Musical Interface Construction. - Vallis, Owen; Kapur, Ajay (Leonardo Music Journal, 2011)
The advent of on-line communities has democratized the process of musical interface design and allowed users to directly participate in the future development of the devices they use. On-line communities, acting as centralized repositories for information pertaining to the development of an interface, allow users to discuss their experiences and ideas as well as providing a framework for managing information pertaining to an interface. This centralized access to information regarding the design, use and development of an interface both focuses and accelerates the developmental process.